2022
DOI: 10.3390/biom12101525
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Delivery Platform for Veterinary Ophthalmology—A New Concept for Advanced Ophthalmology

Abstract: Cyclosporine A (CsA) is a selective and reversible immunosuppressant agent that is widely used as a medication for a wide spectrum of diseases in humans such as graft versus host disease, non-infectious uveitis, rheumatoid arthritis, psoriasis, and atopic dermatitis. Furthermore, the CsA is used to treat keratoconjunctivitis sicca, chronic superficial keratitis, immune-mediated keratitis and equine recurrent uveitis in animals. The selective activity of Cyclosporine A (CsA) was demonstrated to be an immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…59 Based on the values obtained in Figure 6, the sample composed only of electrospun PLDLA presented a contact angle measurement with distilled water of 130 (± 2.2 ), confirming its hydrophobic character. Contrary to previous observations, Padjasek et al 61 and Zych et al 62 indicated that PLDLA film samples exhibit contact angles of approximately 70.9 (± 2.1 ) and 75.5 (± 3.6 ), respectively. Similar results were observed by Wimpenny, Ashammakhi, and Yang, 63 where the PLDLA film presented a less hydrophobic character compared with the electrospun material.…”
Section: Contact Angle Measurementmentioning
confidence: 62%
“…59 Based on the values obtained in Figure 6, the sample composed only of electrospun PLDLA presented a contact angle measurement with distilled water of 130 (± 2.2 ), confirming its hydrophobic character. Contrary to previous observations, Padjasek et al 61 and Zych et al 62 indicated that PLDLA film samples exhibit contact angles of approximately 70.9 (± 2.1 ) and 75.5 (± 3.6 ), respectively. Similar results were observed by Wimpenny, Ashammakhi, and Yang, 63 where the PLDLA film presented a less hydrophobic character compared with the electrospun material.…”
Section: Contact Angle Measurementmentioning
confidence: 62%
“…CsA is a lipophilic, cyclic undecapeptide weighing 1202.6 g/mol MW, with poor solubility in water and limited bioavailability [ 10 ]. As a drug, it is used in human and veterinary medicine transplantation procedures as well as the broad spectrum of immune-mediated inflammatory diseases (IMIDs) due to its strong immunosuppressive potency [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclosporin A is a selective and reversible immunosuppressive agent that is widely used as a drug for a wide spectrum of human diseases, such as graft-versus-host disease, noninfectious uveitis, rheumatoid arthritis, psoriasis, and atopic dermatitis [10]. Clinically, the gingival lesion induced by ciclosporin A is characterized by hyperemia, bleeding both during probing and brushing, or even spontaneous bleeding.…”
Section: Introductionmentioning
confidence: 99%